Answer:
x= 15 and y= 11
Explanation:
The goal here is to solve
x + y =26 and
3x + y =56 for the variables x and y.
First, let's work on your first equation, x + y =26
After this initial survey of the equations, the system of equations we'll set out to solve is:
x+y = 26 and 3x+y = 56
Let's start by solving x+y = 26 for the variable x.
Move the y to the right hand side by subtracting y from both sides, like this:
From the left hand side:
y - y = 0
The answer is x
From the right hand side:
The answer is 26-y
Now, the equation reads:
x = 26-y
To isolate the x, we have to divide both sides of the equation by the other variables
around the x on the left side of the equation.
and this is the final solution to your equation.
Next, let's solve 3x+y = 56 for the variable y.
Move the 3x to the right hand side by subtracting 3x from both sides, like this:
From the left hand side:
3x - 3x = 0
The answer is y
From the right hand side:
The answer is 56-3x
Now, the equation reads:
y = 56-3x
To isolate the y, we have to divide both sides of the equation by the other variables
around the y on the left side of the equation.
and this is the final solution to your equation.
Now, plug the earlier result, x=26-y, in for x everywhere it occurs in
y=56-3x.
This gives y=56-3(26-y). Now all we have to do is solve this for y,to have our first solution.
26-y evaluates to 26-y
Multiply 3 by 26-y
we multiply 3 by each term in 26-y term by term.
This is the distributive property of multiplication.
Multiply 3 and 26
1
3 × 26 = 78
Multiply 3 and -y
Multiply 1 and y
The y just gets copied along.
y
3 × -y = -3y
3*(26-y) evaluates to 78-3y
56 - 78 = -22
The answer is -22+3y
56-3*(26-y) evaluates to -22+3y
Move the 3y to the left hand side by subtracting 3y from both sides, like this:
From the left hand side:
y - 3y = -2y
The answer is -2y
From the right hand side:
3y - 3y = 0
The answer is -22
Now, the equation reads:
-2y = -22
To isolate the y, we have to divide both sides of the equation by the other variables
around the y on the left side of the equation.
The last step is to divide both sides of the equation by -2 like this:
To divide y by 1
The y just gets copied along in the numerator.
The answer is y
-2y ÷ -2 = y
-22 ÷ -2 = 11
The solution to your equation is:
y = 11
Lastly, to find the solution for x, we plug this answer for y into the earlier result that
x=26-y.
This gives x=26-(11). Now, simplify this.
26-(11) evaluates to 15
x= 15
So, the solutions to your equations are:
x= 15 and y= 11